Patterns of psychoactive substance use among two-wheel commercial riders in Maiduguri, Borno state, Nigeria (2011)
When any psychoactive substance is taken before driving, lives of both passengers and other motorists operating on the highway are endangered. This survey study designed to determine the patterns of psychoactive substance use among two-wheel commercial riders in Maiduguri, Borno State, Nigeria. The population of this study was 4141 two-wheel commercial riders operating in Maiduguri, Borno State. Multi-stage sampling technique was used to select 18 substations from the sampling frame. However, only 297 respondents constituted the study sample. Data were collected with the help of research assistants using a questionnaire. Descriptive statistics were used to analyze the data generated. The results of the study reveal that the commonly used psychoactive substances were kola nyt, cigarette, alcohol and marijuana. Oral and sniffing were the routes used by the respondents. Seventy-five percent of the respondents used these substances daily, mostly kola nut (31.31%) and cigarette (24.24%) that were obtained within garage. Alcohol (8.41%) and marijuana (7.74%) were obtained outside the garage. Analysis of problems associated with psychoactive substance use in the last one year shows that road traffic accident was the highest (Z-value of 6), followed by work and social problems (Z—value of 5 and 4) respectively. It is recommended that an intervention studies be conducted by the government and Non-Governmental Organizations (NGOs) to give the two-wheel commercial riders information on the types, use and consequences of psychoactive substances. Finally, government should enforce laws against psychoactive substance use and provide high-tech tools to help law enforcement agencies to tract substance users